2019
DOI: 10.1002/cncr.32296
|View full text |Cite
|
Sign up to set email alerts
|

Does race predict survival for women with invasive breast cancer?

Abstract: BACKGROUND: Black women with breast cancer have lower survival rates and higher recurrence rates in comparison with white women. This study compared treatment and survival outcomes for black and white women at a highly specialized tertiary care cancer center. METHODS: An institutional review board-approved, retrospective institutional database review was performed to identify all black women treated for invasive breast cancer between 2005 and 2010. Women with a prior history of breast cancer, stage IV cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Clearly, this study by Walsh et al 6 does not obviate the need to address socioeconomic disparities in care.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Clearly, this study by Walsh et al 6 does not obviate the need to address socioeconomic disparities in care.…”
mentioning
confidence: 82%
“…9 Walsh et al 6 found in their study that although TNBC was more common in black women, the incidence of genetic testing was far less frequent, with 10% of black women and 74% of white women undergoing genetic testing. Poly(adenosine diphosphate ribose) polymerase inhibition is promising for patients with germline BRCA mutations and triplenegative disease, and we know that rates of BRCA mutations are much higher in TNBC than estrogen receptor-positive and/or HER2-positive disease.…”
mentioning
confidence: 99%
See 3 more Smart Citations